Socio-Demographic and Clinical Correlates of Exclusive Breastfeeding practices up to Six Months of Age - Mathew, Anil Chankaramangalam; Benny, Jibin K; Philip, Dona Maria; Dhanya, C; Joy, Melvin; Sandhiya, V; Ramesh, S; Neelakandan, K (Nepal Journal of Epidemiology, 2019)
Background: According to the recommendations from The World Health Organization, exclusive breast feeding (EBF) should be given to infants for the first six months for healthy growth and development. However, developing countries have a wide range of variation in the practice of EBF. From this study, we aim to estimate the duration of EBF and find the impact of socio-demographic characteristics on EBF.Materials and Methods: This study was conducted at PSG Institute of Medical Sciences and Research, Coimbatore in the month of July 2018. Mothers with children aged below 4 years attending the paediatric outpatient department were included in the study. Kaplan-Meier curve analysis and logistic regression analysis were employed.Results: Our analysis indicates that the prevalence of EBF was 58.4% among infants up to 6 months of age with mean duration of EBF 4.52 months. It was observed that mothers of a younger age (15-24 years) and with lower socio-economic status were negatively associated with the practice of providing EBF to infants up to six months of age.Conclusion: The findings clearly indicate that the interventions related to EBF up to six months of age should be targeted at women in the lower socio-economic status and at younger ages.